2017
DOI: 10.3389/fchem.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides in Biomedical Device Manufacturing

Abstract: Over the past decades the use of medical devices, such as catheters, artificial heart valves, prosthetic joints, and other implants, has grown significantly. Despite continuous improvements in device design, surgical procedures, and wound care, biomaterial-associated infections (BAI) are still a major problem in modern medicine. Conventional antibiotic treatment often fails due to the low levels of antibiotic at the site of infection. The presence of biofilms on the biomaterial and/or the multidrug-resistant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
185
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(189 citation statements)
references
References 151 publications
(179 reference statements)
2
185
0
2
Order By: Relevance
“…These infections can be difficult to remove and often require complete replacement of the biomedical device, which is not always successful in preventing an infection from re-occurring [58]. Biofilms on biomedical devices can be limited by coating the device surface with peptides [59].…”
Section: Formulation and Therapeutic Delivery Of Anti-biofilm Peptidesmentioning
confidence: 99%
“…These infections can be difficult to remove and often require complete replacement of the biomedical device, which is not always successful in preventing an infection from re-occurring [58]. Biofilms on biomedical devices can be limited by coating the device surface with peptides [59].…”
Section: Formulation and Therapeutic Delivery Of Anti-biofilm Peptidesmentioning
confidence: 99%
“…It is important to note that AMPs display high potency against a broad spectrum of bacteria. Moreover, the mechanism of action of AMPs (i.e., interaction with bacterial membranes) appears to have a lower propensity to develop antibacterial resistance compared to conventional antibiotics . Following this rationale, the functionalization of Ti with an equimolar mixture of an RGD peptide and the AMP HHC36 inhibited the attachment of S. aureus and E. coli while improving BMSC adhesion .…”
Section: Multifunctional Chemical Coatingsmentioning
confidence: 99%
“…A review from 2017 of commercially available catheters identified two main antimicrobial strategies used: silver‐coated (with a range of different forms of silver) and antibiotic‐coated (including nitrofural, sparfloxacin, rifampicin, or minocycline) catheters . Several solutions are currently at research stage and have not yet been clinically tested, such as chlorhexidine‐ or triclosan‐loaded catheters, or catheters with antimicrobial peptides, enzymes, bacteriophages, nitric oxide or zwitterionic coatings, other polymer coatings, or liposomes . In some limited patient groups, the use of antimicrobial catheters has been reported to reduce the incidence of CAUTI, for example, in diabetic insulin‐dependent patients, a high‐risk group for this type of infections .…”
Section: Device‐associated Urinary Tract Infectionsmentioning
confidence: 99%